Associazione ossicodone/naloxone per il trattamento del dolore oncologico severo - Combination of oxycodone/naloxone for severe oncologic pain treatment - Paolo Desio (Publiediting, 2011)
From February to April 2011, 46 patients (27 male and 19 female) suffering from different cancer pain were treated with an association of oxycodone/naloxone. The pain intensity of each patient was assessed by the visual analogue scale (VAS). The measurements were taken at T0 - T15 - T30 - T45 -T60 and T75. The therapy's efficacy, the side effects and the sleep's quality were evaluated. The results observed were: a better control of pain which allows patients to achieve effective self-care with a sooner return to everyday life and a tendency to zero of the side effects (especially the constipation).